Relação entre stakeholders, recursos estratégicos e sustentabilidade em uma organização atuante na cadeia de valor da indústria brasileira de energia eólica - Misticone, Danilo Lopes Alcade (2014)
This paper approaches the strategy in business management and aimed at identifying and outlining the interests and commitment of stakeholders in strategic resources management concerning production and implementation of wind turbine equipment of a Brazilian wind power company and also verifying if internal and external results deriving from such activities were sustainable, taking as main reference seminal publications and periodicals relevant to the research point that discuss the Resource Theory, Stakeholders and Sustainability. An analysis was carried out to assess how stakeholders, beyond the temporal context, intermediated the composition, development and management of the organization´s resources, as well as the social, environmental and economic results obtained from resources management in the production and supply of wind turbines to a Wind Power Plant located in the State of Ceara, in order to portray that Brazil sustainability can be an important competitive advantage source that creates value for shareholders and the community (Hart & Milstein, 2003). The strategy herein applied was the qualitative investigation using a single study case, which allowed for the thorough examination of an active organization operating in the Brazilian industry of wind power and also the resources used in the production and implementation of wind turbines supplied to the a Wind Power Plant in Ceara. Considering the content analysis and the triangulation principle, three qualitative data collection methods were applied to identify and characterize stakeholders’ interest and commitment in resource management of the organization operating in the Brazilian wind power industry, as follows, semistructured deep interview with managers of tactic-strategic level and analysts of organization´s value chain nine activities, analysis of public internal and external documents; and analysis of audio-visual material. Nonetheless, to identify the internal and external economic, social and environmental results of implementation and supply of wind turbines to the Wind Power Plant in Ceara, semistructured interviews were also carried out with the residents of the region. Results showed the BNDES (Brazilian Development Bank) and the organization head office were the stakeholders who exerted the strongest influence on resources related to production and implementation of the aerogenerator product at Trairi Wind Plant in Ceara. Concerning the organization resources, at the current stage of the Brazilian Wind Industry ,although the brand, reliability and reputation of the organization under study were valuable esources, rare, hard to imitate and exploited by the organization, it was noticed that opposed to RBV, they did not actually represent a source of competitive advantage . For the local community the social, economic and environmental results related to the wind turbines implementation were more positive than negative, despite the fact that the productive process caused negative environmental impacts such as the high emission of CO2 to transport wind turbines components to Trairi Wind Power Plant.